Pengaruh substitusi kulit kentang (Solanum tuberosum L.) dalam pembuatan bakso ayam terhadap mutu kimia, kandungan zat besi, dan mutu organoleptik - Ester Nita Fajar Karunia; Athiefah Fauziyyah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Potato processing in food industry leaves the main waste in the form of potato peels. Based on its nutritional value, potato peels has the potential to be used as a food ingredient. 100 g of potato peels contains 115 calories, 19.8 mg of calcium, 7.8 g of vitamin C, 5 g of fiber, and 4.1 mg of iron. Research on mice given potato peelings showed an increase in hemoglobin levels due to the iron content in potato peels. Reduced intake and increased use of iron in the process of preparing red blood cells in the human body are factors that cause anemia that has a significant impact on health. In this study, the use of potato peels (Solanum tuberosum L.) were carried out as a substitute of tapioca for making chicken meatballs and found out its effect on chemical quality, iron (Fe) content, and organoleptic quality. The difference in treatment carried out was the proportion of potato peels substitution; P1 (potato peels substitution 0%), P2 (35%), P3 (70%), and P4 (100%). On chemical quality, P1 (substitution of 0% potato peelings), P2 (35%), P3 (70%), and P4 (100%) in alpha 5% had a significant effect on the content of water (α=0.000), ash (α=0.001), fat (α=0.000), crude fiber (α=0.000), carbohydrates (α=0.000), and energy (α=0.000), except protein (α=0.097) of chicken meatballs. The four treatments had a noticeable difference in the iron content of chicken meatballs. The more proportion of potato peels substitution (Solanum tuberosum L.), the higher the iron content (Fe) of chicken meatballs. Organoleptically, the addition of potato peels did not have a noticeable different effect on the tests of color (α=0.956), appearance (α=0.506), and smell preferences (α=0.134). Meanwhile, the preference test on the parameters of texture (α=0.019), taste (α=0.010), and overall (α=0.002) shows that there was a noticeable difference.